The Bruen Problem: Writing Gun Laws That Can Withstand Constitutional Challenge - Sophia Larson (Washington University Undergraduate Law Review, 2025)
One of the most pressing public policy issues in the United States is gun regulation. An incredibly polarizing topic, it pits those who prioritize the preservation of their constitutional rights against those who prioritize safeguarding the American youth. Advocates for the latter push for more fervent gun legislation, but as the Supreme Court’s decision in New York State Rifle & Pistol Association v. Bruen (2022) clearly holds, many contemporary gun control laws are not legally robust. It is now more critical than ever to write gun control laws that are both effective and capable of withstanding constitutional scrutiny. But how is this achievable in the post-Bruen landscape? Recent legal challenges have exposed ambiguities and pitfalls in the “text, history, and tradition” test, making its application difficult. This paper examines early interpretations of the Second Amendment, the influence of the landmark Bruen decision and its lower court predecessors (including U.S. v. Rahimi), and proposes solutions to drafting gun control legislation that both protects and considers constitutional precedents.
Keywords: Bruen; Gun Control; Second Amendment